An evaluation of effectiveness of Ilizarov external fixation in treating infected non-union tibial fractures: a prospective observational study - Kumar, Ashutosh; Kumar, Rishabh; Shankar, Anand; Kumar, Rakesh (International Journal of Research in Medical Sciences, 2024)
Background: Infected non-union tibial fractures pose significant challenges in orthopedic care. Ilizarov external fixation has emerged as a promising treatment option for such complex fractures. The purpose of this research is to evaluate the efficacy and safety of Ilizarov fixation in non-union, infected tibial fractures. Methods: A prospective observational study was conducted on 30 patients at Indira Gandhi Institute of Medical Sciences. Inclusion criteria involved patients aged 20-65 with clinical and radiological signs of infection and non-union of the tibia. Data on patient demographics, injury details, treatment history, and outcomes were collected. Ilizarov fixation was performed, and patients were followed up. Results: The study cohort, primarily males (80%), with mean age of 35.75 years, displayed a high incidence of type III compound injuries (63.33%). Monofocal and bifocal osteosynthesis effectively reduced limb shortening, with an overall average residual shortening of 1.8 cm. Bony outcomes were favorable, with 16 cases achieving excellence. Functional outcomes were also promising. Complications included stiffness, infections, and deformities. Conclusions: Ilizarov external fixation demonstrates potential in managing infected non-union tibial fractures, offering favorable bony and functional outcomes. However, post-operative complications require vigilant management. Further research is needed to validate and optimize this approach.